Current issues and trends in special education identification, assessment and instruction - Obiakor, Festus E.; Bakken, Jeffrey P.; Rotatori, Anthony F. (Bingley, U.K. : Emerald, 2009)
This is the first of two themed volumes addressing the current issues and trends in Special Education. Volume 19 covers identification, assessment and instruction whilst volume 20 covers research, technology, and teacher preparation. The field of special education constantly changes as a result of legislation, new instructional formats and current research investigations. It can be difficult for general and special educators, school counselors and psychologists, administrators and practicing clinicians to keep up with these changes and be current in all areas relating to special education. The special education literature knowledge base should reflect these changes; however, there is no current resource that effectively and comprehensively does this. The purpose of "Current Issues and Trends in Special Education" is to fill this void, providing chapters written by active researchers and practitioners in their respective areas.
ch. 1. Early identification/intervention : the earlier the better for students with disabilities / Yi-Juin Liu -- ch. 2. Early identification/intervention : can misidentification/misintervention impact students, teachers, and families? / Barbara Metzger, Cynthia G. Simpson, Jeffrey P. Bakken -- ch. 3. Can underidentification affect exceptional learners? / Rhonda S. Black -- ch. 4. Disproportionate representation in special education : overrepresentation of selected sub-groups / Tina Taylor Dyches, Mary Anne Prater -- ch. 5. Standardized testing/accountability : is NCLB fair for students with disabilities? / Tes Mehring -- ch. 6. Curriculum-based assessment : the most effective way to assess students with disabilities / Sunday Obi -- ch. 7. Labeling of students with disabilities : needed for students to get their needs met / Gathogo M. Mukuria, Jeffrey P. Bakken -- ch. 8. Labeling of students with disabilities : unwanted and not needed / Craig Blum, Jeffrey P. Bakken -- ch. 9. The general education classroom : this is not where students with disabilities should be placed / Jeffrey P. Bakken -- ch. 10. Beyond traditional placement : making inclusion work in the general education classroom / Festus E. Obiakor, Mateba K. Harris, Anthony F. Rotatori, Bob Algozzine -- ch. 11. Behaviorism works in special education / Darlene H. Anderson, Michelle Marchant, Nancy Y. Somarriba -- ch. 12. Other innovative techniques : positive behavior supports and response to intervention / John J. Wheeler and Michael R. Mayton -- ch. 13. Scientifically supported interventions / Martha L. Thurlow, Courtney Foster, Christopher M. Rogers -- ch. 14. Scientifically unsupported treatments for students with special needs / Julie A. Deisinger.
Keywords: Education -- Special Education -- General; Criminal justice law; England; Special education